TEACHING MATERIALS DEVELOPMENT BASED ON BASIC COMPETENCE THROUGH DIFFUSION ADAPTATION STRATEGY TO IMPROVE LEARNING PROCESS OF PHYSICS SUBJECT - Ruhiat, Yayat; Hidayat, Sholeh; Suparno, .; Hasani, Aceng; Wibowo, Firmanul Catur (PEOPLE: International Journal of Social Sciences, 2016)
Based on the curriculum of high school education in Indonesia, all senior high school students must be able to acquire all standard competences and basic competences. Unfortunately, most senior high school students in Serang districts, Banten Province, were not able to acquire all standard competences and basic competences operationally. Based on the result of national examination from 2007 to 2013, there were still ten standard competences and basic competences in Physics subject that the students still found difficulties in acquiring the learning materials. It was shown that there were teaching materials which cannot be taught to students due to some teachers’ weaknesses in delivering the teaching materials well. To overcome those problems, the researcher developed some teaching materials of Physics subject to be implemented by Physics teachers in Serang districts and city, Banten Province.The researcher used Diffusion Adaptation Strategy (DAS) in order to gather all Physics teachers from Serang districts-Banten Province, Indonesia. The result of the study showed that the teaching materials development with DAS had feedback mechanism towards several level of improvement with the three positive loops. Through Diffusion Adaptation Strategy (DAS), the teachers can acquire the teaching materials very well in 72.6% of improvement, the teachers can also improve their academic and knowledge of Physics teaching materials in 68.3% of improvement, and finally the teachers can improve the learning process of Physics subject in 74.8% of improvement. The teaching materials development through DAS can produce the teachers who can acquire the teaching materials very well, able to use the teaching media, and able to implement various kinds of teaching methods while they are teaching Physics subject in the classroom. Based on the curriculum of high school education in Indonesia, all senior high school students must be able to acquire all standard competences and basic competences. Unfortunately, most senior high school students in Serang districts, Banten Province, were not able to acquire all standard competences and basic competences operationally. Based on the result of national examination from 2007 to 2013, there were still ten standard competences and basic competences in Physics subject that the students still found difficulties in acquiring the learning materials. It was shown that there were teaching materials which cannot be taught to students due to some teachers’ weaknesses in delivering the teaching materials well. To overcome those problems, the researcher developed some teaching materials of Physics subject to be implemented by Physics teachers in Serang districts and city, Banten Province. The researcher used Diffusion Adaptation Strategy (DAS) in order to gather all Physics teachers from Serang districts-Banten Province, Indonesia. The result of the study showed that the teaching materials development with DAS had feedback mechanism towards several level of improvement with the three positive loops. Through Diffusion Adaptation Strategy (DAS), the teachers can acquire the teaching materials very well in 72.6% of improvement, the teachers can also improve their academic and knowledge of Physics teaching materials in 68.3% of improvement, and finally the teachers can improve the learning process of Physics subject in 74.8% of improvement. The teaching materials development through DAS can produce the teachers who can acquire the teaching materials very well, able to use the teaching media, and able to implement various kinds of teaching methods while they are teaching Physics subject in the classroom.